The Voices of Primary School Boys and Girls on Human Rights and Their Historical Agency - López Martínez, Manuel José; Jiménez Martínez, Mᵃ Dolores (Frontiers in Education, 2022)
The teaching of History in primary school must integrate education for active global citizenship in the face of inequalities and social injustice caused by the constant violation of human rights in the present. The transformative framework at school promotes global citizenship from a humanizing perspective and a respect for diversity. All of this comes in a context marked by the effects of the capitalist economic dimension of globalization, which translates into a crisis in the exercising of fundamental democratic values. Below, we show the first-phase results of educational research comprising a qualitative exploratory study that investigates what primary school students think about and know. The participants come from a public school in the city of Almería, south-eastern Spain. Given the volume of information obtained from the semi-structured group interviews conducted on a total of 126 students (male and female) and seven teachers at the school, a qualitative content analysis has been carried out to extract relevant meaning regarding the research objectives; these focused on what the students know and feel about human rights, social problems and injustices, and the role of girls and boys throughout history. Hearing, listening to and recognizing the voices of primary school boys and girls has provided us, first of all, with ethical cues to design professional teacher development experiences in line with the new times of change and uncertainty, from the framework of a critical teaching of the contents of school history. Secondly, it has guided us in the configuration of training opportunities to cover the weaknesses caused by the democratic deficit and strengthen democracy by increasing child citizen participation. In this way, we hope to contribute to the education of a global citizenry that is more critical and committed to the common good in collective decision-making in an interconnected world.